Predictors of anxiety and depression among HIV infected pregnant mothers on antiretroviral therapy attending antenatal clinics at leading teaching and referral hospitals in Kenya - Osman, Abdihakim M.; Nyamu, David Gitonga; Amugune, Beatrice Kagai (International Journal Of Community Medicine And Public Health, 2025)
Background: Poor maternal psychological health in pregnancy has a detrimental effect on the socio-emotional development of the unborn child and should therefore be assessed and mitigated. The study aimed at establishing the level of anxiety and depression among mothers on antiretroviral therapy attending antenatal clinics at Mbagathi and Kenyatta National Hospitals. Methods: A descriptive cross-sectional study among 70 HIV infected mothers attending antenatal clinics. Anxiety and depression were determined using the Generalized Anxiety Disorder-7 and Patient Health Questionnaire-9 tools, respectively. Statistical analysis was done using IBM Statistical Package for Social Sciences version 23 with p<0.05 considered statistically significant. Binary logistic regression was done to find out independent predictors of anxiety and depression among the participants. Results: The mean age of the study participants was 32.3 (SD 5.78) years. Most participants attained at least a secondary school education level (47.1%) and were married (75.7%). The overall prevalence of anxiety was 23.8% with minimal, mild, moderate and severe anxiety at 52.9%, 34.3%, 4.3% and 8.6%, respectively. The overall depression rate was 22.6% with minimal, mild, moderate, moderately severe and severe depression at 42.9%, 32.9%, 15.7%, 2.9% and 5.7% respectively. There was statistically significant association between anxiety and depression (p= 0.025) but no statistically significant association between sociodemographic variables and anxiety or depression. Conclusions: There was a considerable level of anxiety and depression among the mothers. Anxiety and depression were positively related. Therefore, counselling, psychosocial education and multidisciplinary team management should be integrated into the management of HIV infected mothers.